A Meta-Synthesis of Ethics-Aware Software Engineering Practice: A Preliminary Framework - Senyeki Milton Marebane; Ernest Mnkandla (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
The use of evidence-based practice to inform ethical software development is important for all stakeholders to achieve successful software and address the ethical needs of those affected by it. Although research exists on various mechanisms for supporting ethical software development, their integration into a framework that enables expansive ethics awareness and adherence is lacking. This study fills this gap by conducting a qualitative metasynthesis of studies that implemented and evaluated mechanisms to support ethics in software development. Meta-ethnography methodology was followed and supported by the PRISMA reporting guidelines to achieve the study's objective. Most of the mechanisms identified in the four selected studies are oriented toward supporting the integration of ethics into software development in the artificial intelligence domain, rather than the broader software engineering ethics spectrum. The study contributes a conceptual framework for ethics-aware software engineering practice. The proposed framework requires empirical validation. In addition, Further studies are required to explore other resources reporting on other transformative technologies to expand the framework for improving the software engineering practice.